Hormone Receptors, Her-2/Neu and Chromosomal Aberrations in Breast Cancer - Dutta, V (Med J Armed Forces India, 2008)
BACKGROUND: There is a great deal of disparity in the incidence of breast cancer in rural and urban India on one hand and between India and Western population on the other. METHODS: We analysed steroid receptor status in cases of breast cancer in a small sample of patients in armed forces. Infiltrating duct carcinomas of breast recorded histologically in mastectomy specimens in last two years were accessioned in the present study with reference to patient and tumour characteristics. RESULT: In contrast to the higher rates reported in western literature, only 33 % of the tumours expressed estrogen receptors (ER) and progesterone receptors (PR), of which 24% were ER positive and 30% PR positive. Negative steroid receptor status did not correlate with presence or absence of metastatic nodes, however it was predominant amongst the high grade infiltrating duct carcinomas in this study. Necrosis and lymphovascular invasion demonstrated an inverse relationship with the ER/ PR reactivity. 70% of the node positive cases expressed Her –2/ Neu, reflecting a higher immunoreactivity in this subset of patients. Aneusomy for chromosomes 1, 11 and 17 was common in node positive cases. CONCLUSION: Evaluation of chromosomal aberrations by Fluorescent In Situ Hybridization (FISH) technique correlates well with traditional histological parameters.